SMALL NAVY, BIG RESPONSIBILITIES: THE STRUGGLES OF BUILDING INDONESIA’S NAVAL POWER - I Gusti Bagus Dharma Agastia (AEGIS : Journal of International Relations, 2017)
From its inception, the Indonesian Navy (TNI-AL) has struggled to reconcile its relatively small capabilities with its large responsibilities. This paper argues that significant reforms need to be carried out in order to improve the overall capacity of the TNI-AL and build Indonesian naval power. The Global Maritime Fulcrum vision provides this opportunity, however, it must be sustained by the political leadership in the long term as developing naval power does not happen overnight. To that end, this paper discusses four chief problems that the TNI-AL continues to face today, namely (1) a lack of a comprehensive maritime outlook, (2) stringent budgetary conditions, (3) a continental-oriented command and control structure, and (4) “turf wars” between related agencies in the government. This paper also briefly contrasts and compares Indonesia’s experience with China’s experience with naval development under Hu Jintao and Xi Jinping. Although both countries are arguably different from one another in one way or the other, this exercise serves to highlight three lessons that may be applicable for Indonesia in managing its naval development and understanding the complexity in building its naval power. These lessons include (1) a need for strong and sustained political will in developing naval power and (2) having a clear strategic objective for naval development, and (3) a significant amount of resources are required to build naval power.